ORGANIZATIONAL CULTURE AS A POINT FACTOR IN CREATING ORGANIZATIONAL DEVELOPMENT - Ardiana Trisnawiana (SEAN Institute, 2023)
Corporate culture is considered to have the power to influence change, making it a driving force for company growth. The purpose of this research is to ascertain how important organizational culture is in promoting healthy organizational development. The research method used in this study is a qualitative research technique and data analysis for literature review. The results of this study indicate that organizational culture has both beneficial and unfavorable influences on organizational sustainability between employees and leaders. Company culture influences the perspectives, attitudes, and behaviors of employees that are relied on and used in everyday tasks, such as getting work done. When negative cultural attitudes are developed, they have an effect on how the organization operates. A new approach is needed in organizational development to obtain more comprehensive and reliable information regarding the relationship between organizational culture and organizational development.